(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2026)
This study integrates sedimentological, petrographic, and magnetic fabric analyses of the Tithonian deposits of the Vaca Muerta Formation exposed in the southern sector of the sierra de la Vaca Muerta. The sedimentological analysis allowed the identification of four facies associations (FA) and two depositional environments. FA1 comprises distal outer carbonate ramp deposits, FA2 represents mixed outer ramp deposits, and FA3 belongs to turbiditic events. These FA correspond to the lower member of the unit and constitute a mixed carbonate–siliciclastic outer ramp system. FA4 comprises the whole Los Catutos Member, and it is interpreted as outer carbonate–ramp deposits. Magnetic mineralogy studies, together with mean magnetic susceptibility values and the dominant mineralogical composition indicate a paramagnetic influence (clays, muscovite, biotite) as the primary control on the AMS properties. IRM studies indicate a minor contribution of ferromagnetic particles, such as titanomagnetite and hematite. The AMS study enabled the recognition of sedimentary fabrics, as well as inverse fabrics and petrofabrics related to post-depositional processes. Sedimentary fabrics include horizontal fabrics related to hemipelagic settling mechanisms and flow-aligned fabrics associated with flat-bed and current-ripple migration processes. Inverse fabrics are attributed to the presence of ferroan calcite while post-depositional fabrics include mechanisms such as bioturbation and dolomitization. Flow-aligned fabrics allowed the determination of two paleocurrent data sets: one trending towards NW, composed of sandy turbiditic intervals, and another perpendicular to it, trending SW–NE to E–W. The first case represents sedimentary processes that evolved across-slope while the second case implies the action of along-slope currents. Sedimentary features of these deposits, such as current-ripple lamination, erosional cut-and-fill surfaces, intraclastic fabrics, and bioturbated horizons, might infer the presence of long-lived, along-slope currents, like contour-currents. Thus, these results support recent hypotheses proposing the influence of contour-currents along the slope zone within the clinoform system during the Tithonian.